A multi-wavelength mid-IR laser based on BaGa4Se7 optical parametric oscillators - Ying, Deng (Frontiers in Physics, 2023)
A multi-wavelength mid-IR laser consisting of 3.05 μm, 4.25 μm, and 5.47 μm BaGa4Se7（BGSe）optical parametric oscillators (OPOs) switched by DKDP electro-optic switches with one 10 Hz/7.6 ns pumping wave is demonstrated. Maximum energies at 3.05 μm, 4.25 μm, and 5.47 μm are 1.35 mJ, 1.03 mJ, and 0.56 mJ, respectively, corresponding to optical-to-optical conversion efficiencies of 9.4%, 7.6%, and 4.2%. To the best of our knowledge, this study is the first of generation of three mid-IR wavelength lasers using electro-optic switches. Furthermore, this study provides a viable solution for a high-energy or high-power, compact, or even portable multi-wavelength mid-IR laser device that employs a single pumping wave.